DEVELOPMENT OF A PREPARATION PROCESS FOR DRY EXTRACT POWDER FROM THE MODIFIED NHAT QUAN TIEN FORMULA (Vietnam Journal of Community Medicine, 2026)
Objective: Process development and quality evaluation of dry extract powder derived from the modified Nhat Quan Tien formula (NQT).            Methods: Dry extract powder of the modified Nhat Quan Tien formula (consisting of Rehmannia glutinosa, Glehnia littoralis, Melia azedarach, Angelica sinensis, Lycium sinense, Ophiopogon japonicus, Alisma plantago-aquatica, Phellodendron amurense, Bupleurum chinense, Eurycoma longifolia) was prepared using spray–drying technology. Evaluation of several quality parameters of the dry extract powder including: organoleptic characteristics, particle fineness, total ash, acid-insoluble ash, qualitative identification of saikosaponin A and berberine, moisture content, bulk density, compressibility index (CI), and the contents of saikosaponin A and berberine.            Results: The preparation process of the liquid extract from the modified Nhat Quan Tien was performed using a hot extraction method with 50% ethanol as the extraction solvent. The herb-to-solvent ratio was 1:10 (g/ml), extraction temperature was maintained at 60°C, and extraction was conducted for 60 min and repeated twice. The extract was concentrated at 70–80°C under a vacuum pressure of 60–70 mmHg to obtain the modified Nhat Quan Tien extract with a concentration ratio of 3:1. The optimal conditions for spray-drying to obtain the dry extract powder included a spray-drying carrier system consisting of maltodextrin and aerosil (15:85), with a carrier-to-solid ratio of 30%, the inlet temperature was 140°C, the feed rate was 30 ml/min, and the compressed air pressure was 2 bar. The quality parameters of the obtained dry extract powder were as follows: the powder exhibited a free-flowing and dry appearance, light brown color, and a characteristic odor of the herbal formula; the powder was classified as a very fine powder; the average total ash content was 3,21%; and the average acid–insoluble ash content was 0,37%; saikosaponin A and berberine were qualitatively identified by HPLC; the average moisture content was 3,53%; bulk density was 0,86 g/ml; and compressibility index (CI) was 32,91%; the contents of saikosaponin A and berberine were 4,6 mg/g (RSD% = 1,63%) and 74,89 mg/g (RSD% = 1,35%) respectively.            Conclusion: A preparation process for dry extract powder from the modified Nhat Quan Tien formula was successfully developed, and several quality parameters of the obtained powder were evaluated. The resulting dry extract powder met the investigated quality criteria. These findings provide a scientific basis for the development of pharmaceutical products derived from the dry extract powder prepared from the modified Nhat Quan Tien formula.
Keywords: Dry extract powder, Nhat Quan Tien, Spray drying